Antioxidant Properties of Pyrus communis and Pyrus pyrifolia Peel Extracts - Vinda Maharani Patricia; Fauzia Ningrum Syaputri; Titian Daru Asmara Tugon; Athina Mardhatillah (Borneo Journal of Pharmacy, 2020)
With the rise of global health awareness by embracing a healthy lifestyle and natural product consumption, the search for natural antioxidant sources has invited more research performed especially in fruits as a whole product or in its components, especially the ones that are usually discarded/not the mainly consumed component. Pyrus communis and Pyrus pyrifolia are two of the most popular species of pear fruits consumed in the world, and while there exist several studies about the antioxidant potential of its flesh, specific studies about the antioxidant properties of their peels are still lacking. To achieve an understanding of antioxidant properties of peel extract of P. communis and P. pyrifolia, several tests have been performed in controlled laboratory conditions to gauge phenolic and flavonoid contents through three different extraction measurements. This research has shown that peel extracts of both P. communis and P. pyrifolia contain natural antioxidants that are beneficial for health, with P. communis extracted with methanol having a higher concentration of antioxidant contents compared to P. pyrifolia.